Effect of immunosuppressive therapy on interferon γ release assay for latent tuberculosis screening in patients with autoimmune diseases: a systematic review and meta-analysis. Issue 1 (11th December 2015) - Wong, Sunny H; Gao, Qinyan; Tsoi, Kelvin K F; Wu, William K K; Tam, Lai-shan; Lee, Nelson; Chan, Francis K L; Wu, Justin C Y; Sung, Joseph J Y; Ng, Siew C
Abstract : Objective: Interferon γ release assay (IGRA) is commonly used to diagnose latent TB infection (LTBI). Immunosuppressive therapy may affect its performance but data are conflicting. We aimed to determine the effect of immunosuppressive therapy on the performance of IGRA in patients with autoimmune diseases. Methods: We searched PubMed, MEDLINE, EMBASE and the Cochrane Library up to December 2014. We included studies that reported the IGRA results in patients with autoimmune disease with or without immunosuppressive therapy. The pooled effect of immunosuppressive therapy on IGRA was estimated using a Peto fixed-effects model. Results: We included 17 studies with 3197 participants in the meta-analysis. Among the subjects, 71.5% were taking immunosuppressive therapy and 56.7% had received Bacillus Calmette–Guérin vaccination. Compared with patients not on immunosuppressants, patients receiving immunosuppressive therapy were less likely to have a positive IGRA result (OR 0.66, 95% CI 0.53 to 0.83, I 2 =23%), especially patients receiving anti-tumour necrosis factor (anti-TNF) treatment (OR 0.50, 95% CI 0.29 to 0.88). The use of immunosuppressive therapy was also associated with a lower rate of positive tuberculin skin test result (OR 0.51, 95% CI 0.42 to 0.61). Conclusions: Our meta-analysis showed that IGRA results are negatively affected by immunosuppressive therapy. IGRA alone may not be sufficiently sensitive to diagnose LTBI in patients on immunosuppressive therapy. Patients should preferably be screened for LTBI before initiation of immunosuppressive therapy, especially before anti-TNF therapy.